2020
DOI: 10.15252/embj.2020105666
|View full text |Cite
|
Sign up to set email alerts
|

Structures of IS C th4 transpososomes reveal the role of asymmetry in copy‐out/paste‐in DNA transposition

Abstract: Copy-out/paste-in transposition is a major bacterial DNA mobility pathway. It contributes significantly to the emergence of antibiotic resistance, often by upregulating expression of downstream genes upon integration. Unlike other transposition pathways, it requires both asymmetric and symmetric strand transfer steps. Here, we report the first structural study of a copy-out/paste-in transposase and demonstrate its ability to catalyze all pathway steps in vitro. X-ray structures of ISCth4 transposase, a member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…Because MULEs are poorly characterized in nematodes, we predicted the structure of the C. briggsae MULE transposase using AlphaFold2 ( 33 ) and identified the residues that make up its characteristic DDE motif catalytic triad based on structural homology to IS Cth4 , a prokaryotic transposase of the IS256 family related to eukaryotic MULEs (fig. S6) ( 34 ). These three residues (Asp 21 , Asp 83 , and Glu 198 ) were perfectly conserved in MULE transposases from 49 different nematodes species, including HK104, suggesting that the transposase linked to msft-1 is functional (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because MULEs are poorly characterized in nematodes, we predicted the structure of the C. briggsae MULE transposase using AlphaFold2 ( 33 ) and identified the residues that make up its characteristic DDE motif catalytic triad based on structural homology to IS Cth4 , a prokaryotic transposase of the IS256 family related to eukaryotic MULEs (fig. S6) ( 34 ). These three residues (Asp 21 , Asp 83 , and Glu 198 ) were perfectly conserved in MULE transposases from 49 different nematodes species, including HK104, suggesting that the transposase linked to msft-1 is functional (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that IstA is active using either a mixture of TIRs or just the isolated left or right TIR. More precisely, the activity with the left end was mildly reduced (~2-fold), whereas the activity using the right end was equivalent to that seen for the mixture of both TIRs (it has been shown that other transposases can use the isolated left and right ends with varying degrees of efficacy 46 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand this, we built a truncated version of the IS256 Tnp and showed that it is inactive ( Fig 2F ). Previous work has shown that similarly truncated IS256 variants are able to bind to the element’s IRs, but structural studies indicate that this truncation likely loses key dimerization domains essential for transposition [ 79 , 80 ]. We hypothesize that IS256 Tnp site 2 binds to the IRs to prevent full-length IS256 Tnp from binding and activating transposition.…”
Section: Discussionmentioning
confidence: 99%